Pelatihan Pembuatan Konten dan Promosi Produk di BUMDes Sumber Rejeki Desa Karangkemojing - Hellyana, Corie Mei; Fadlilah, Nuzul Imam; Widayanto, Aprih; Saifudin, Saifudin; Pristi, Anisa Nur; Astuti, Yeni Dwi; Risalief, Arbhat (LPPM Universitas Bina Sarana Informatika, 2023)
BUMDes Sumber Rejeki Desa Karangkemojing is a business activity managed by the apparatus of Karangkemojing Village, Gumelar District, Banyumas Regency. These BUMDes exist with the aim of improving the standard of living and economy of rural communities. For now, the products in BUMDes Sumber Rejeki are coffee products. Based on the results of interviews with the management of Sumber Rejeki BUMDes by doing business and helping the community introduce home industrial products or household-scale businesses in the area of Karangkemojing Village, it is possible for other products to be provided or deposited in Sumber Rejeki BUMDes, so that the industrial products of the people of Karangkemojing Village are better known to the wider community. Based on this case, the community service group (PM) and Sumber Rejeki BUMDes collaborated with to hold content creation and product promotion training utilizing the Canva application and Google MyBusiness to help Sumber Rejeki BUMDes introduce MSME and home industry products online. The results obtained by participants in PM were able to get to know, utilize and use the Canva application to create content and then upload it to social networks for product promotion and marketing tools.